DNA methylation as a tumor marker: implications for diagnosis, early detection and risk assessment - Belinsky, Steve (Henry Stewart Talks, 2010)
How genes are silenced epigenetically via cytosine methylation and chromatin remodeling, Assays for detecting gene promoter methylation in biological fluids, Challenges for developing methylation-based assays, Lung cancer case-control study of gene promoter methylation in sputum, Predicting risk for lung cancer through gene methylation detection in plasma, Gene promoter methylation as a diagnostic tool for lung, colon, prostate, and bladder cancer